Characterization of the measurement uncertainty for the electromagnetic conducted and radiated emission test - Ayob, Mohd Erdi (2017)
Electromagnetic Compatibility or EMC is the ability for the product or equipment under test (EUT) able to operate in its intended environment with causing undue interference or being unduly affected by it. The requirement for non-interference has been known for many years but it is only now with the introduction of legislation that we are seeing a major growth in demand for testing. The USA with its FCC regulations uncertainty ULAB= 2uc(y). The thesis focused the application of the expanded uncertainty deployment for the judgement criteria for the finalize EUT status.